PENGGUNAAN BERBAGAI KOMPOS KOTORAN TERNAK TERHADAP PERTUMBUHAN Pennisetum purpureum cv. Pakchong - Rahmi Dianita; Murdianingsih Murdianingsih; Mario Genesia; Abdur Rahman (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
Manure derived from cattle, chickens, and goats can be used as compost and has different nutrient content. The application of manure compost can improve soil’s physical, chemical, and biological properties and thus increase plant growth and productivity. The purpose of this study was to determine the effect of various manure compost (cow, chicken, and goat) on the growth of elephant grass cv Pakchong (Pennisetum purpureum cv. Pakchong). The design used was a completely randomized design with 4 treatments and 5 replications. The treatment is fertilizing using compost, namely P0= without compost, P1=cow manure compost, P2=chicken manure compost, and P3=goat manure compost. The observed variables were plant height, the number of leaves and tiller, and the dry weight of the leaves stem shoots and roots. The results showed that the use of manure compost had a significant effect (P<0.05) on increasing the growth of elephant grass cv. Pakchong. Chicken manure compost produces the best growth of elephant grass cv. Pakchong which is seen from the plant height, the number of leaves and tiller, and the dry weight of the leaves, stems, and shoots.